Impact of Technology Assisted Education for Improving Learning Skills - Eftekhairul, Md; Mishra, M. S (International Journal of Computer Sciences and Engineering, 2025)
This paper takes an initiative to show how the technology and technology based system and approach towards education has impacted learning any language as well as acquiring linguistics skills. To attain effectiveness in learning and acquiring the language related skills & awareness, a number of methods are being used but those methods without technologies are rarely successful to the beginners and adult learners. Mostly, technologies in education such as Computer Assisted Language Learning (CALL) & Mobile Assisted Language Learning (MALL) have kept widely influenced to the Technology Assisted Education (TAE). TAE has a close relationship with modern science and technology in this regard. Not only inside but also outside the classroom, Teaching associated with TAE helps instructors and the young and the adult learners using the MALL technology. Smart Information technologies have made the classroom educative, skillful and informative. TAE makes both the teachers and the students skillful in the regard of language learning by smart-innovative and modern technologies. It teaches them how to manage the time; to get information and to earn knowledge. At last visualization adds a new era in the language learning system